The Effect of Lembaga Penjamin Simpanan Deposit Guarantee Implementation on Dual Rural Bank’s Stability in Indonesia - Moh. Najikhul Fajri; Andini Kusumawardhani (Politeknik Caltex Riau, 2026)
Main Purpose - This study examines the role of deposit insurance in enhancing the stability of conventional and Islamic rural banks (BPR and BPRS) under economic uncertainty. Method – A quantitative approach is employed using a dynamic panel data model, analyzing data from 1,266 BPRs and 113 BPRSs between 2013 and 2019. The Generalized Method of Moments (GMM) is applied to account for persistence in bank stability and potential endogeneity between deposit insurance and stability. Main Findings – The results show that ethical climate has a positive effect on trust and a negative effect on organizational misidentification and workplace bullying. Employees who perceive a stronger ethical climate tend to have higher trust and lower negative workplace behaviors. The findings also provide preliminary evidence that trust mediates the relationship between ethical climate and negative workplace behaviors. Theory and Practical Implications – The findings suggest that deposit insurance alone does not guarantee bank stability; it operates effectively when combined with sufficient capitalization. Policymakers and bank managers should ensure strong bank fundamentals to maximize the protective role of deposit insurance, especially under economic uncertainty. Novelty – This study uniquely investigates how economic uncertainty conditions the interaction between deposit insurance, capitalization, and bank stability, focusing on the often-overlooked BPR and BPRS sector.